Drug Delivery: A Bioinspired Platform for Effective Delivery of Protein Therapeutics to the Central Nervous System (Adv. Mater. 18/2019). Issue 18 (2nd May 2019) - Wu, Di; Qin, Meng; Xu, Duo; Wang, Lan; Liu, Chaoyong; Ren, Jie; Zhou, George; Chen, Chen; Yang, Fengmei; Li, Yanyan; Zhao, Yuan; Huang, Ruyi; et al.
Abstract : A universal central nervous system (CNS)‐delivery platform is developed enabling the delivery of protein therapeutics to the brain via choline transporters and acetylcholine receptors. In article number1807557, Zhanlong He, Jing Wen, Wei Chen, Yunfeng Lu, and co‐workers demonstrate that the protein therapeutics can effectively penetrate the blood–brain barrier in mice and nonhuman primates by encapsulating the proteins within nanocapsules with choline and acetylcholine analogues.